Ethics and Governance in the Upanishads: A Framework for Modern Leadership (Poornaprajna International Journal of Management, Education & Social Science (PIJMESS), 2025)
Purpose: The Upanishads, ancient Indian philosophical texts, are often revered for their profound metaphysical insights. However, beyond their spiritual teachings, they offer valuable ethical principles and governance models that remain relevant in contemporary leadership contexts. This paper explores the ethical framework embedded in Upanishadic philosophy, focusing on concepts such as Dharma (righteousness), Satya (truth), self-awareness, and non-attachment (Vairagya). By examining dialogues and teachings from key Upanishads, particularly the Brihadaranyaka, Chandogya, and Katha Upanishads, this study identifies principles that can inform modern leadership practices, including ethical decision-making, servant leadership, sustainability, and value-based governance. Methodology: In this paper, the exploratory qualitative research method is used. The relevant information is collected using keyword-based search in Google search engine, Google Scholar search engine, and AI-driven GPTs. This information is analysed and interpreted as per the objectives of the paper. Analysis/ Results: Ultimately, the Upanishadic framework bridges the gap between ancient wisdom and contemporary leadership practices, offering enduring lessons on how to lead with integrity, compassion, and a sense of higher purpose. By revisiting these ancient texts, modern leaders can cultivate ethical governance models that foster not just organizational success but also social harmony and human flourishing.Originality/ Values: The comparative analysis highlights how the Upanishadic emphasis on inner transformation, integrity, and selfless action (Nishkama Karma) offers a timeless framework for leaders navigating complex ethical dilemmas in today’s globalized, dynamic environments.
Keywords: Upanishads; Ethics; Governance; Modern Leadership; Dharma; Satya; Nishkama Karma; Value-Based Leadership; Servant Leadership; Ancient Philosophy